The Relationship Between Sleep Quality and Bedtime With the Incidence of Acne Vulgaris Among 11th Grade Students at SMAN 4 Kendari - Indah Sayyidatul Annisa; Siti Andayani; I Putu Sudayasa; Edy Husnul Mujahid; Yenti Purnamasari; Nelly Herfina Dahlan (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2025)
Background: Acne vulgaris is an inflammatory disease of the pilosebaceous unit that commonly affects adolescents and young adults. The causes of acne vulgaris are multifactorial, involving various internal and external factors, among which sleep quality and bedtime are significant contributors. Poor sleep quality and late bedtime may lead to a decrease in melatonin levels. Reduced melatonin levels can result in increased androgen hormone synthesis, which in turn stimulates sebaceous gland activity and contributes to the development of acne vulgaris. Purpose(s): This study aims to determine the relationship between sleep quality and bedtime with the incidence of acne vulgaris among 11th-grade students at SMAN 4 Kendari. Methods: This study is an observational analytic research with a cross-sectional approach. The sampling method used was simple random sampling, involving a total of 90 students. Data on sleep quality and bedtime were collected through questionnaires, while the incidence of acne vulgaris was assessed through facial screening. Data were analyzed using the chi-square statistical test. Results: Based on the results of the chi-square test using statistical software, a p-value of 0.01 was obtained. A p-value <0.05 indicates that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Conclusion: There is a relationship between sleep quality and bedtime with the incidence of acne vulgaris among 11th-grade students at SMAN 4 Kendari (p-value = 0.01).